Pengaruh agama Islam terhadap sistem hukum adat Madura: Sinkretisme dan interaksi budaya - Amartha, Feni Putri (Maliki Interdisciplinary Journal, 2023)
The Madurese have a strong tradition of customary law that has been rooted in their daily lives since ancient times. However, along with the entry of Islam into Madura, there was a process of interaction between Islamic values ​​and the tradition of Madurese customary law. Through a qualitative approach, where the data collection method was carried out by comparative analysis in the influence of Islam on Madurese customary law, whether it comes from legal practice customs, norms, and values ​​in society as a method of collecting data. The results of the research show that the influence of Islam on the Madurese customary law system creates a complex cultural syncretism. There is an amalgamation of Islamic religious values ​​with the tradition of Madurese customary law in legal practices, rituals and social activities. In the process of cultural interaction, Islamic religious norms influence the interpretation and application of Madurese customary law, while the values ​​and practices of Madurese customary law also influence the understanding and implementation of Islamic teachings among the Madurese community. In this change, it can be seen that there is a role for the ulema and religious leaders in linking Madurese customary law with Islamic religious teachings. They provide guidance and fatwa in interpreting and applying customary law to conform with Islamic values. The role of the ulama also facilitates dialogue between customary law and Islam and plays a role in resolving disputes based on Islamic principles. In conclusion, the influence of Islam on the Madurese customary law system creates cultural syncretism and complex interactions between Islamic religious values ​​and the Madurese customary law tradition. This interaction reflects the dynamic adaptation of society in maintaining cultural heritage while integrating Islamic religious values ​​into their legal practices and social life.